Characteristics of the patients with adnexal torsion and outcomes of different surgical procedures: A retrospective study. Issue 5 (February 2019) - Wang, Zengyan; Zhang, Dan; Zhang, Huanxiao; Guo, Xu; Zheng, Jingxuan; Xie, Hongzhe
Abstract : Abstract: There is no uniform standard to assess the viability of the ovary and choose conservative surgery or radical surgery for patients with adnexal torsion. This retrospective study aims to explore the characteristics of patients with adnexal torsion and the outcomes of different surgical procedures. A retrospective analysis of 174 cases diagnosed with adnexal torsion at our hospital between January 2005 and October 2014 was performed. Patients' clinical characteristics, surgical procedures, and postoperative recovery were analyzed. Of the cases, 31 (17.82%) did not have any emergent symptom; adnexal torsion were found during other surgeries. Among all 174 adnexal torsion patients, 14 cases received conservative treatment, including anti-inflammatory treatment, and 8 (58.1%) were pregnant. Of the cases, 160 underwent surgical treatment: 144 (90%) were confirmed to have ovary/ovarian cyst torsion, among whom 26 (18.1%) had their adnexa retained (group A) and 118 (81.9%) underwent adnexectomy (group B). Age, time of torsion, and rounds of torsion in group A were significantly less than in group B. None of the patients with adnexa preservation surgery had any complication, such as abdominal infection or thrombotic diseases. Patients with ovary/ovarian cyst torsion can attempt to preserve the ovaries without serious clinical complications; there were no severe complications such as embolism after the conservative surgeries in this study.